Endogenous preferences, emotions, and the breaking of social capital into economics - Martti Vihanto (Aboa Centre for Economics (ACE), 2007)
The creation and effects of social capital have seldom been a target for systematic analysis in orthodox economics. The purpose of the paper is to argue that in order to include social capital, along with physical and human, into economic analysis, we have to regard human preferences as endogenous and pay more attention to the contents rather than merely the logic of choice and decisionmaking. The paper limits itself to examining the role of trust in the formation and disruption of social capital. Emotions such as guilt and shame are central in the emergence of trust within social relations. Sources of and means to strengthen trustworthiness are examined in the context of bank loans.
Keywords: B52; D11; O17; 330; social capital; trust; endogenous preferences; emotions; behavioural economics; bounded rationality